Comparison of the Internet Literacy of Youths and Their Parents for Evidence-Based Youth Protection - Nagayuki Saito; Madoka Aragaki (International Telecommunications Society (ITS), 2017)
A contemporary problem in societies is that of youths becoming involved in various online troubles. For enhancing Internet literacy, providing support to not only youths but also their parents has become a major policy challenge. This study evaluated and analyzed the Internet literacy of youths and parents to discuss effective policy making, as defined in Article 3 of the supplementary provision of the “Act on Establishment of Enhanced Environment for Youth's Safe and Secure Internet Use.” The results revealed that parents had significantly higher Internet literacy than youths did, according to the total score and subscores in each risk category. However, for questions related to “online game billing” and “understanding of the `Act on Regulation on Soliciting Children by Using Opposite Sex Introducing Service on Internet,'” high school students performed better than their parents did. Therefore, it is crucial to provide support for enhancing parents' literacy regarding unfamiliar risks.
Keywords: 330